Downward nominal house price rigidity: Evidence from three centuries of data on housing transactions - Solveig K. Erlandsen; Ragnar Enger Juelsrud (Norges Bank, 2023)
By analyzing housing data from the period 1850 to 2019 in Norway, we find evidence of downward nominal house price rigidity. More specifically, we document that there is a marked fraction of repeat-sales housing transactions with a zero nominal price change and show that this fraction increases in housing market downturns. While the former result reveals a rigidity in nominal house prices, the latter suggests that the direction of it is predominantly downward.
hdl:11250/3042518
Keywords: R31; E30; N13; N14; 330; House prices; Repeat sales transaction data; Price rigidity; Monetary policy; Financial crisis